2018
DOI: 10.1016/j.envres.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of informal electronic waste recycling on metal concentrations in soils and dusts

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The methods employed in this study have been well detailed in our previous studies [8,16,35,36]. In brief, a cross-sectional study design was adopted to gain an understanding of the pollution levels at the e -waste recycling sites in the three study locationsin Nigeria: Ibadan, Lagos, and Aba.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods employed in this study have been well detailed in our previous studies [8,16,35,36]. In brief, a cross-sectional study design was adopted to gain an understanding of the pollution levels at the e -waste recycling sites in the three study locationsin Nigeria: Ibadan, Lagos, and Aba.…”
Section: Methodsmentioning
confidence: 99%
“…High concentrations of metals and PBDEs were found at and around informal e -waste recycling sites [35,36,37,38,39,40]. Large quantities of e -waste are informally recycled in Nigeria using various recycling activities such as repair, dismantling, and open burning [41].…”
Section: Introductionmentioning
confidence: 99%
“…The highest levels of metals were detected in soils from the Agbogloshie e-waste processing site, as well as neighbouring residential, recreational, farming, and commercial areas [97], with the highest level found in the area where waste burning occurs. Isimekhai et al [93] and Ohajinwa et al [98] also found an increase in metals levels at ewaste recycling sites in Nigeria, which was dependent on the type/intensity of the recycling activity. Metal levels increased from the repair sites to dismantling sites and the highest levels were detected in the burning sites.…”
Section: Metals/metalloids Contamination In Different Environmental Cmentioning
confidence: 91%
“…The methods employed in this study have been well detailed in our previous studies [32]. In brief, this study was conducted in three study locations/cities in Nigeria as depicted in the map as A,B,C, which are Ibadan, Aba, and Lagos respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 presents a schematic flow diagram of the sample collection from the various e-waste sites in the three study locations. In the previous study by Ohajinwa et al [32] which was on metal pollution at the same sites, a total of 62 samples. While for this study, a total of 56 samples consisting of 16 top soils (0–10 cm), 29 floor dust, five roadside dust, and six direct dust samples (collected from the inside and outside of electronic devices) were analysed.…”
Section: Methodsmentioning
confidence: 99%